Final results of the randomized phase 2 LEO trial and bone protective effects of everolimus for premenopausal hormone receptor‐positive, HER2‐negative metastatic breast cancer. Issue 4 (7th May 2021) - Jeong, Hyehyun; Jeong, Jae Ho; Kim, Jeong Eun; Ahn, Jin‐Hee; Jung, Kyung Hae; Koh, Su‐Jin; Cheon, Jaekyung; Sohn, Joohyuk; Kim, Gun Min; Lee, Keun Seok; Sim, Sung Hoon; Park, In Hae; et al.
Abstract: The phase 2 LEO study showed that everolimus (EVE) plus letrozole (LET) with ovarian suppression increased progression‐free survival (PFS) in tamoxifen‐exposed premenopausal women with hormone receptor‐positive, HER2‐negative metastatic breast cancer with visceral metastases. Here we report final survival outcomes from the LEO study, and the results of exploratory analyses of bone turnover marker changes and bone‐specific progressive disease. Patients who were exposed to or progressed on tamoxifen as adjuvant/palliative treatments were randomly assigned (2:1) to the EVE (leuprorelin + LET + EVE, n = 92) or LET (leuprorelin + LET, n = 45) arm. In a median 51‐months of follow‐up, the median PFS was 17.5 and 13.8 months in the EVE and LET arms, respectively ( P = .245). Patients in the EVE arm with baseline visceral (median PFS 16.4 vs 9.5 months, P = .040) and bone (median PFS 17.1 vs 10.9, P = .003) metastases had greater PFS compared to the LET arm. No differences in overall survival (OS) were observed (median OS, 48.3 vs 50.8 months, P = .948). The 1‐year cumulative incidences of bone‐specific disease progression were 6.0% and 23.4% in the EVE and LET arms, respectively (hazard ratio 0.26, P < .001). Bone turnover markers at 6 and 12 weeks after treatment decreased in the EVE arm but were increased or stationary in the LET arm. Skeletal‐related events occurred in 6.5% and 11.1% of patients in the EVE and LET arms, respectively. EVE + LET with ovarian suppression prolonged PFS in patients with baseline visceral or bone metastases and offered bone‐protective effects in the overall study population. However, these clinical benefits did not translate into an OS benefit. Abstract : What's new? In the phase 2 LEO study, women with hormone receptor‐positive, human epidermal growth factor receptor 2‐negative metastatic breast cancer with visceral metastases who were previously treated with tamoxifen, experienced significant improvements in progression‐free survival following combination therapy with the protein kinase inhibitor everolimus and the aromatase inhibitor letrozole. This report describes final survival outcomes from the LEO study. Patients with visceral or bone metastases treated with combined leuprorelin, letrozole, and everolimus survived longer with progression‐free disease compared to women who received leuprorelin and letrozole. Regimens employing everolimus were associated with reductions in bone turnover, bone‐specific disease progression, and skeletal‐related events, suggesting a role for everolimus in bone protection.